Modelagem da formação e propagação de trincas em misturas betuminosas através do método dos elementos finitos - Freitas, Felipe Araújo Colares de (2002)
Cracking in the asphaltic layers has been pointed out as the major pavement distress in Brazilian roadways. Typically, no consideration for the material heterogeneity has been given on previous studies. This work presents a numerical method of analysis, based on the theoryof fracture mechanics, in which the asphaltic mixture is considered heterogeneous. The binder and the aggregates are treated as separate elements. The simulations performed can be verified and calibrated with simple and conventional laboratory tests. The study investigates crack formation and evolution under monotonic loading. Nevertheless, it also outlines a new method of analysis for fatigue of asphaltic mixtures. It is also discussed the use of a multiscale methodology, in which the damage due to cracking in the local scale can be considered in a global analysis at the actual pavement scale.